A história inventando moda: a influência da memória na criação de coleções de moda com referência no passado (ModaPalavra e-periódico, 2010)
This paper aims at putting into question the influence of historical references in the creation of new clothing collections, herein referred to as fashion. Based upon questioning and research on present time memory, which intends to understand the need for presentifying the past, the goal of this study is to understand how fashion keeps the past always present. The ideas here described look out to better comprehend fashion as an object that identifies associations between elements in the past, in relation to the experience of the present.
Keywords: History; Memory; Fashion